Sojourn: in the soul of India - Chugh, Smita (New Delhi, 2009)
The book is a collection of anecdotes describing the author$1 (Bs experience of working in rural India as an IAS officer and the issues which cropped up as she focused on technology interventions, among other concerns, in these areas. s
Keywords: Memoirs-Civil Servents